2009 IEEE International Symposium on Circuits and Systems 2009
DOI: 10.1109/iscas.2009.5118036
|View full text |Cite
|
Sign up to set email alerts
|

Sub-threshold operation and cross-hierarchy design for ultra low power wearable sensors

Abstract: This paper examines the requirements of wearable sensing applications and their implications for designing the next generation of body area sensors. We define key metrics for wearable sensors and discuss how body area sensors differ from generic wireless sensors. To explore the system level issues with a wearable node, we show measurements from a wearable electrocardiogram (ECG) sensor prototype. Using heart rate monitoring as an example, we show how ultra low power (ULP) circuit design must be applied to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…With advances in Internet of Thing (IoT) applications and the expansion of mobile devices, energy consumption has become a primary focus of attention in integrated circuits design [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While IoT applications cover a broad range of products from wearable devices, smart houses, automotive devices, smart meters to inspection tools and many others, more than 50% of the market is dominated by battery operated devices.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in Internet of Thing (IoT) applications and the expansion of mobile devices, energy consumption has become a primary focus of attention in integrated circuits design [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While IoT applications cover a broad range of products from wearable devices, smart houses, automotive devices, smart meters to inspection tools and many others, more than 50% of the market is dominated by battery operated devices.…”
Section: Introductionmentioning
confidence: 99%
“…In extreme cases, the combination of process and temperature variations can even cause certain circuits to malfunction. Therefore, specific measures need to be taken to deal with this drawback.Sub-threshold and near-threshold circuits have received a lot of attention in the research community during the last decade [6-8,10-13] with successful ultra-low voltage chip implementations: microprocessors [6,8,[10][11][12], as well as dedicated ASICs for biomedical applications [7,13,[33][34][35][36], for wireless sensor nodes [10,15,17,[37][38][39], communication [40,41], image processing [42,43], RFIDs [44] and many others. While previous research indicated significant power reduction and successful minimum energy operation, it did not present complete MCU SoC solutions that are suitable for mass production.This paper presents a 40 nm MCU System-on-a-Chip (SoC), which includes the complete Synopsys ARC EM5D core MCU and features a full set of DSP instructions [29].…”
mentioning
confidence: 99%
“…For example, a wireless ECG monitor could derive heart rate, or detect instances of cardiac arrhythmia, rather than transmitting the complete ECG signal. This often has the effect of reducing the total power consumption, because wireless data transmission is frequently the dominant consumer of power in a wireless sensor, and the energy expended to perform feature detection and compression can frequently be made less than the energy saved by reducing the amount of data to be transmitted [24] [25].…”
Section: Wireless Sensor Architecturementioning
confidence: 99%